Gerador de sinais microcontrolado - Araújo, Marcelo Ferreira de (2013)
The present study shows the development project of a sinusoidal, square, and sawtooth electric waveform generator, with configurable frequency from a specific generator IC, and a control logic elaborated in a microcontroller applied programming language. The entire process was developed by a computational tool, allowing closeness of the virtual model with the final project. Once the best component configuration was chosen, it was possible, through another computational tool, to create the project's hardware.